Reduire les expressions:

A=10x-5-4-6x+x+8+10-5

B=8y+9x-8-2y-7x-4y+5x-8-6x

C=10y+10y-2y-5+y-6-2x-9

D=-x+4+4+10y+9y-10y-8y+2y

Reduire et ordonner les expressions:

A=-1-7+7x²+3+6x+5+4x-4x²+5+3x+9-1

B=x-6x²+8x²-2x+9x²+4x²+2x²+5-4

C=10-3x²+10-3x²+8x+3x²-3x²+8x²-8x-10x-6

D=-5+8x²+8x-3x+10x-10-4x+3x-x+7+9x+4x

1

Réponses

Meilleure réponse !
2012-09-23T15:27:36+02:00

A= 10x-5-4-6x x 8 10-5
= (10x-6x+x)+(-5-4+8+10-5)
= 5x+4

B= 8y 9x-8-2y-7x-4y 5x-8-6x
= (8y-2y-4y)+(9x-7x+5x-6x)+(-8-8)
= 2y+x-16

C= 10y 10y-2y-5 y-6-2x-9
= (10y+10y-2y+y)+(-2x)+(-5-6-9)
=19y-2x-20

D= -x 4 4 10y 9y-10y-8y 2y
= (-x)+(4+4)+(10y+9y-10y-8y+2y)
= -x+3y+8


et j'ai pas compris comment ordonner les expressions.